Dairy cows affected by ketosis show alterations in innate immunity and lipid and carbohydrate metabolism during the dry off period and postpartum. (August 2016) - Zhang, Guanshi; Hailemariam, Dagnachew; Dervishi, Elda; Goldansaz, Seyed Ali; Deng, Qilan; Dunn, Suzanna M.; Ametaj, Burim N.
Abstract: The objective of this investigation was to search for alterations in blood variables related to innate immunity and carbohydrate and lipid metabolism during the transition period in cows affected by ketosis. One hundred multiparous Holstein dairy cows were involved in the study. Blood samples were collected at − 8, − 4, week of disease diagnosis (+ 1 to + 3 weeks), and + 4 weeks relative to parturition from 6 healthy cows (CON) and 6 cows with ketosis and were analyzed for serum variables. Results showed that cows with ketosis had greater concentrations of serum β-hydroxybutyric acid (BHBA), interleukin (IL)-6, tumor necrosis factor (TNF), serum amyloid A (SAA), and lactate in comparison with the CON animals. Serum concentrations of BHBA, IL-6, TNF, and lactate were greater starting at − 8 and − 4 weeks prior to parturition in cows with ketosis vs those of CON group. Cows with ketosis also had lower DMI and milk production vs CON cows. Milk fat also was lower in ketotic cows at diagnosis of disease. Cows affected by ketosis showed an activated innate immunity and altered carbohydrate and lipid metabolism several weeks prior to diagnosis of disease. Serum IL-6 and lactate were the strongest discriminators between ketosis cows and CON ones before the occurrence of ketosis, which might be useful as predictive biomarkers of the disease state. Highlights: Both PCA and PLS-DA indicated two clear separated clusters of healthy and ketotic cows. Serum BHBA, IL-6, TNF, and lactate were greater starting at − 8 and − 4 weeks prior to parturition in ketotic cows. Cows with ketosis experienced lower DMI and elevated milk SCC. Serum IL-6 and lactate might be useful as predictive biomarkers of the disease state.